Pelagic Jurassic and Cretaceous beds in the western part of the Julian Alps - Jurkovšek, Bogdan; Šribar, Ljudmila; Ogorelec, Bojan; Kolar-Jurkovšek, Tea (Geologija, 1988)
Jurassic and Cretaceous beds described in this paper are restricted to relatively minor areas of some square kilometers occurring on the Mangart pass, at Plešivec, Bavšica, Vrsnik and at Čisti Vrh. They overlie transgressively the older beds and are tectonically delimited for the most part. Jurassic and Cretaceous beds at these localities are pelagic sediments, with exception of some Lower Lias neritic limestones. Their variegated appearance testifies to a active tectonics in the time interval between the Lower Jurassic and the Upper Cretaceous as well as to sedimentation environments, which developed in the aftermath of the destruction of the Julian Carbonate platform during the Liassic.